Stabilisability analysis and design of UDE‐based robust control. Issue 10 (1st May 2019) - Tian, Zhen; Zhong, Qing‐Chang; Ren, Beibei; Yuan, Jingqi
Abstract : The uncertainty and disturbance estimator (UDE)‐based robust control approach is widely investigated and applied due to its excellent performance and simple implementation. However, its stabilisability of unstable systems has not been documented. In this study, the sufficient and necessary stabilisability conditions of the UDE‐based robust control are investigated. According to the stabilisability conditions, a systematical design method is presented for the reference model based on the controllable canonical transformation and pole placement. This is then applied to a magnetic levitation system (MagLev) subject to model uncertainties and external disturbance as an example. Simulation results are presented to illustrate the effectiveness of the proposed control approach with respect to matched uncertainties.